The Impact of Fintech adoption on the regional innovation efficiency: Empirical evidence from Jordan (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:           With the growing trend of fintech in the previous years, it has become the central point of attention for many researchers. The objective of this study is to examine the effect of fintech on the innovation efficiency by using the data on governorates level of Jordan. The two stage DEA method is used to assess innovation efficiency. Spatial Durbin Model is used for the empirical analysis. It is found that fintech has a positive effect on overall efficiency and launching efficiency but have a very little impact on the research and development efficiency.it is also observed that in launching phase, fintech has a spatial spillover effect.